1990
DOI: 10.1530/jrf.0.0900439
|View full text |Cite
|
Sign up to set email alerts
|

Tissue concentration, mRNA expression and stimulation of IGF-I in luteal tissue during the oestrous cycle and pregnancy of cows

Abstract: The expression of IGF-I in bovine luteal tissue was demonstrated by parallel measurement of IGF-I tissue concentration and its mRNA; highest synthesis was observed during Days 12-17 of the cycle and the first months of pregnancy. Tissue levels of IGF-I increased from Days 1-5 to Days 12-17 of the cycle followed by a rapid decrease at luteolysis; there was a continuous decline from early pregnancy until Months 6-9. Microdialysis perfusion experiments with corpora lutea in vitro at Days 8-11 of the cycle reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 6 publications
2
41
0
Order By: Relevance
“…These trends were confirmed by RPA (ribunoclease protection assay) and localization of the proteins [56]. The bovine corpus luteum in general has been shown to express IGF-1 mRNA [57][58][59][60][61]. In most cases CL were collected from day 5 onwards.…”
Section: Igf In Bovine Corpus Luteummentioning
confidence: 69%
“…These trends were confirmed by RPA (ribunoclease protection assay) and localization of the proteins [56]. The bovine corpus luteum in general has been shown to express IGF-1 mRNA [57][58][59][60][61]. In most cases CL were collected from day 5 onwards.…”
Section: Igf In Bovine Corpus Luteummentioning
confidence: 69%
“…Indeed, GH increases ovarian levels of IGF-I in vitro in rats [26] and rabbits [27]. Moreover, in vitro studies have shown that IGF-I stimulates the secretion of P and OT from the CL of ewes [28] and cows [29][30][31]. We immunocytochemically examined the possibility that GH may directly increase IGF-I production in luteal cells surrounding the microcapillary mem- brane in the cyclic ewes used in experiment 1.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I promotes FSH and LH supported steriodogenesis on follicular cells, LH receptor induction, and inhibin synthesis [2,36]. It is also a potent in vitro stimulator of the release of progesterone in cultures of bovine luteal cells or intact tissues [30,51,76]. In the steroidogenic pathway IGFs have been shown to stimulate the aromatase system [3,24].…”
Section: Endocrine Effects Of Igf-i On Reproductive Functionmentioning
confidence: 99%